(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides an in-depth analysis of the role and importance of foreign languages, particularly English, in the professional activities of athletes. In the context of globalization, sport is becoming not only a means of physical preparation but also a field that encompasses intercultural communication and international exchange of experience. Under such circumstances, knowledge of a foreign language enables athletes to successfully participate in international competitions, access scientific and technical information, and communicate effectively with coaches and other athletes. The article highlights an integrative approach to language teaching for athletes based on modern educational methods such as CLIL, PBL, and TBL. It also presents the outcomes of practical experiments, surveys, and the analysis of experimental textbooks conducted in sports educational institutions in Uzbekistan, thereby substantiating the real results of language learning.